LGG-31. SUSTAINED OBJECTIVE RESPONSE TO DABRAFENIB THERAPY ACROSS DIFFERENT BRAIN HISTOLOGIES HARBOURING BRAF V600E ACTIVATING MUTATION. Issue 2 (22nd June 2018) - Sumerauer, David; Krskova, Lenka; Kyncl, Martin; Zapotocky, Michal; Kuklova, Adela; Zamecnik, Josef; Ondrova, Barbora; Stary, Jan
Abstract: Paediatric low-grade gliomas are the most common brain tumours in children. They are characterized by alterations of the Ras/MAPK pathway. Gliomas harbouring BRAF activating mutations were repeatedly shown to respond to BRAF inhibition. We present our experience with dabrafenib monotherapy in four patients with low grade gliomas harbouring activating V600E BRAF mutation. RESULTS: Two patients were treated at the time of disease diagnosis, two at the time of disease progression. Although various histologies (PA, PXA, GG), age (6 months, 13 months, 27 months and 8 years) and primary locations (OPG, thalamus, brainstem) were encountered, in all cases dabrafenib treatment at the dose 5.25 mg/kg/day resulted in rapid and profound radiologic response with clinical improvement. All patients are on therapy for 15, 11, 11 and 9 months without any documented toxicity to date. CONCLUSION: Dabrafenib is active and well tolerated among patients with BRAF V600E mutation positive paediatric low-grade gliomas. Rapid responses of tumours to BRAF inhibition may have input on some of their feared sequelae (i.e. visual impairment), not prevented with other therapies to date.